The effect of casein and calcium containing paste on plaque pH following a subsequent carbohydrate challenge - Caruana, Paul Chetcuti; Mulaify, Sami Al; Moazzez, Rebecca; Bartlett, David (Journal of dentistry, 2009)
Previous research has shown that regular use of CPP–ACP increases calcium and inorganic phosphates in plaque and reduces enamel mineral loss. The aim of this study was to investigate if a CPP–ACP-containing paste would neutralize acidic challenges in dental plaque following sucrose rinse. Plaque pH was measured on 15 subjects in a cross-over study with and without prior application of the paste and with and without CPP–ACP. On each occasion, subjects rinsed with 10% sucrose and sorbitol solutions for 2 min in randomized order. The results showed the median lowest pH without paste was 4.8 (IQR: 4.7–5.0) and with mousse 5.6 (IQR: 5.5–5.6 and p < 0.001). The median lowest pH was 5.0 (IQR: 4.9–5.3) without CPP–ACP and with CPP–ACP was 5.8 (5.6–6.1 and p < 0.001). The time that pH remained below 5.7 and the time to return to resting pH showed similar differences in all subjects ( p < 0.01). The results indicate that prior application of a CPP–ACP-containing paste reduced the fall in plaque pH following a sucrose challenge.